Pengaruh Kompetensi Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Negeri Sipil Dinas Pendidikan Provinsi DKI Jakarta - Wiratama, Petrus; Ekawaty, Novian (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of competence and emotional intelligence on the performance of civil servants at the DKI Jakarta Provincial Education Office. The method used in this research is quantitative with a descriptive and verification approach. The sample used in this study was 125 using a probability sampling technique, namely the Proportionate Stratified Random Sampling Technique. The data analysis technique used is analysis by testing the hypothesis partially and simultaneously. Testing is assisted with the SPSS tool. The results of this study are that there is a relationship between competence and emotional intelligence that has a strong relationship. Partially, competence has an effect of 15.1% and emotional intelligence of 50.5% on employee performance. Competence and emotional intelligence have a positive and significant effect on employee performance.